NHS Values, Compassion and Quality Indicators for Relationship Based Person-Centred Healthcare; Comment on "Morality and Markets in the NHS" - John Cox (Kerman University of Medical Sciences, 2015)
The paper by Gilbert et al. should be on the table of every politician and National Health Service (NHS) manager in the run up to the general election, when the NHS is at the hustings. They have raised profound moral dilemmas of the internal and external market in their present form, such as the practicalities of distributive justice and the enhancement of autonomy - to which are added the preservation of personhood, the values of listening, the maintenance of altruism and the origins of compassion. It is asserted that the quality of healthcare is dependent on the quality of the caring relationship between healthcare staff members, and between staff and patients. The nature of Compassionate Resilience is outlined with respect to Health Visitor training - and the contribution of faith communities to public health is also considered. The four Quality Indicators of an enabling environment first proposed by Cox and Gray are summarised, and the need for increased conceptual clarity of these key values recognised.